2023
DOI: 10.1007/s10072-023-06999-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of globus pallidus internus and subthalamic nucleus in Parkinson’s disease: a multicenter, retrospective study of efficacy and safety

Michele Mainardi,
Dario Ciprietti,
Manuela Pilleri
et al.

Abstract: Background Deep brain stimulation (DBS) is an established therapeutic option in advanced Parkinson’s disease (PD). Literature data and recent guidelines remain inconclusive about the best choice as a target between the subthalamic nucleus (STN) and the globus pallidus internus (GPi). Materials and methods We retrospectively reviewed the clinical efficacy outcomes of 48 DBS-implanted patients (33 STN-DBS and 15 GPi-DBS) at a short- (<1 year from the surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The prominence of the Gpi in the study was not surprising. It is highly associated with motor symptoms and therefore with UPDRS-3 score [ 25 ]. Deep brain stimulation of Gpi has also been shown to be effective in improving motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prominence of the Gpi in the study was not surprising. It is highly associated with motor symptoms and therefore with UPDRS-3 score [ 25 ]. Deep brain stimulation of Gpi has also been shown to be effective in improving motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Deep brain stimulation of Gpi has also been shown to be effective in improving motor symptoms. Moreover, it has been demonstrated that Gpi has a greater impact on motor fluctuations and motor experiences of daily living [ 25 ]. The Gpi results may be associated with the correlated role of both Gpi and STN in motor excitatory and inhibitory processes.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of adverse impact between brain regions indicated that targeting the STN relatively worsened the condition of apathy compared to GPi-DBS 29 . Retrospective studies comparing DBS in STN and GPi in PD show improvement on short-term motor symptoms, yet among STN-DBS treated patients there were incidence of suicide and impact on mood and quality of life 30,31 .…”
mentioning
confidence: 99%